1983
DOI: 10.1007/bf00379699
|View full text |Cite
|
Sign up to set email alerts
|

The role of adult feeding in egg production and population dynamics of the checkerspot butterfly Euphydryas editha

Abstract: Carbohydrate intake increases longevity, body weight maintenance and egg production in female Euphydryas editha. Amino acid intake leads to heavier eggs, larvae from which are more likely to survive. Females fed nectar produce more eggs in later masses than females which are not fed. During years of normal and below normal precipitation, larvae emerging from these later eggs are unlikely to reach obligatory size for diapause before their food dries up. On Jasper Ridge, where mortality is density-independent, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
3
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(151 citation statements)
references
References 23 publications
6
141
3
1
Order By: Relevance
“…Usinger [43] also, observed a correlation between food intake and egg production and longevity, although longevity was not studied in this research, a correlation between food intake and egg production was observed. Similar observations were recorded in other insect species; the checker-spot butterfly (Euphydryas editha) had increased egg production and egg mass with increased consumption of carbohydrates and nectar [44]. In previous studies, [45,46] consumption of caffeine was shown to cause mortality in insects.…”
Section: Discussionsupporting
confidence: 82%
“…Usinger [43] also, observed a correlation between food intake and egg production and longevity, although longevity was not studied in this research, a correlation between food intake and egg production was observed. Similar observations were recorded in other insect species; the checker-spot butterfly (Euphydryas editha) had increased egg production and egg mass with increased consumption of carbohydrates and nectar [44]. In previous studies, [45,46] consumption of caffeine was shown to cause mortality in insects.…”
Section: Discussionsupporting
confidence: 82%
“…This prediction can easily be tested, and some authors have demonstrated a positive correlation between maternal body size and the size of the first egg mass spawned in lepidopteran species (Murphy et al 1983, Begon & Parker 1986. My data indlcate the relationships between maternal body size and egg size, potential egg number, and weight of egg mass of Haloa japonica are as predicted by the model (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…It may be that the adult is actually feeding before oviposition. Evidence from a lepidopteran herbivore shows that carbohydrate intake by the adult female increases longevity, body weight maintenance, and egg production (Murphy et al 1983). It is likely that this factor may contribute to the first two hypotheses to produce the pattern of leaf mining on bittercress plants between sun and adjacent shade habitats.…”
Section: -mentioning
confidence: 99%